Use of N‐acetylcysteine during liver procurement: A prospective randomized controlled study. Issue 2 (26th September 2012) - D'Amico, Francesco; Vitale, Alessandro; Piovan, Donatella; Bertacco, Alessandra; Ramirez Morales, Rafael; Chiara Frigo, Anna; Bassi, Domenico; Bonsignore, Pasquale; Gringeri, Enrico; Valmasoni, Michele; Garbo, Greta; Lodo, Enrico; et al.
<x xml:space="preserve">Abstract</x> Antioxidant agents have the potential to reduce ischemia/reperfusion damage to organs for liver transplantation (LT). In this prospective, randomized study, we tested the impact of an infusion of N‐acetylcysteine (NAC) during liver procurement on post‐LT outcomes. Between December 2006 and July 2009, 140 grafts were transplanted into adult candidates with chronic liver disease who were listed for first LT, and according to a sequential, closed‐envelope, single‐blinded procedure, these patients were randomly assigned in a 1/1 ratio to an NAC protocol (69 patients) or to the standard protocol without NAC [71 patients (the control group)]. The NAC protocol included a systemic NAC infusion (30 mg/kg) 1 hour before the beginning of liver procurement and a locoregional NAC infusion (300 mg through the portal vein) just before cross‐clamping. The primary endpoint was graft survival. The graft survival rates at 3 and 12 months were 93% and 90%, respectively, in the NAC group and 82% and 70%, respectively, in the control group (P = 0.02). An adjusted Cox analysis showed a significant NAC effect on graft survival at both 3 months [hazard ratio = 1.65, 95% confidence interval (CI) = 1.01‐2.93, P = 0.04] and 12 months (hazard ratio = 1.73, 95% CI = 1.14‐2.76, P ≤ 0.01). The incidence of postoperative complications was lower in the NAC group (23%) versus the control group (51%, P < 0.01). In the subgroup of 61 patients (44%) receiving suboptimal grafts (donor risk index > 1.8), the incidence of primary dysfunction of the liver was lower (P = 0.09) for the NAC group (15%) versus the control group (32%). In conclusion, the NAC harvesting protocol significantly improves graft survival. The effect of NAC on early graft function and survival seems higher when suboptimal grafts are used. Liver Transpl 19:135–144, 2013. © 2012 AASLD.